On acquiring a complex personal reference system: experimental results from Thai children with autism - Chanchaochai, Nattanun (ZAS Papers in Linguistics, 2018)
Reference of pronouns may be constrained via lexical presuppositions, including marked F-features, implicated presuppositions, and deictic center shifting in certain languages. This paper explores the acquisition of personal reference terms in Thai, a language that has a highly complex personal reference system. The participants of the study were 67 typicallydeveloping children (TD) and 29 children with autism spectrum disorders (ASD), a population which has long been observed to have difficulties with pronouns. The children were asked to complete simple production and comprehension tasks on personal reference terms. Overall, ASD children performed on par in production but significantly poorer in comprehension than TD children. Given the freedom of choice in the production task, ASD children preferred using fixed referential terms for self-reference, whereas TD children opted for personal pronouns. In terms of comprehension, ASD children were shown to generally be able to detect the person features but they seemed to struggle the most with the pragmatic aspects of personal reference terms. Our results support previous literature that lexical presuppositions are acquired earlier than implicated presuppositions. We add to the literature that the types or the amount of implicated presuppositions matter in acquisition. Keywords: implicated presupposition, pragmatic inference, pronoun, personal reference, acquisition, deixis, Thai